The THE MAPPING OF ACTION VERBS IN ‘PELUKIS’ TRANSLATED INTO ‘PAINTER’: THE MAPPING OF ACTION VERBS IN ‘PELUKIS’ TRANSLATED INTO ‘PAINTER’ - Dewa Made Agustawan (Focus Journal : Language Review, 2021)
This research focus on the translation of action verbs applying the Natural Semantic Metalanguge (NSM) approach proposed by Wierzbicka (1996), in case where the source language is Indonesia and the target language is English. Meanwhile, descriptive qualitative approach was applied in which the data were analyzed by explaining descriptively in paraphrases. Initially, the action verbs were identified in both source language (SL) text and target language (TL) text. Then, the meanings of the action verbs were mapped comprehensively into English by adopting exponential mapping technique and explication. The action verbs are derived from the small collection of semantic primitive 'DO' which is categorized as the prototypical concept of ACTION; DO, HAPPEN, MOVE, PUT, and GO.